1955
DOI: 10.1007/bf02640385
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature solubilities of fatty acids in selected organic solvents

Abstract: Summary A number of highly purified fatty acids have been prepared and their solubilities determined in six common organic solvents within the temperature range from 10° to −70°. The acids studied were palmitic, stearic, oleic, elaidic, petroselinic, petroselaidic, linoleic, stearolic, arachidic, eicosenoic, behenic, erucic, and brassidic. The solvents used were methanol, ethyl acetate, diethyl ether, acetone, toluene, and n‐heptane, representing six different solvent types. A limited study was also made with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

1956
1956
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…The relationship between solubility and rate of activation of long chain fatty acids is unclear. Kolb and Brown concluded that solubility of the A6 and A9 cis-octadecenoates was proportional to the distance of the double bond from the carboxyl group (9). However the increased solubility that would result as the double bond is moved from carbon 9 to carbon 17 would not be correlated with the activation profile observed in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…The relationship between solubility and rate of activation of long chain fatty acids is unclear. Kolb and Brown concluded that solubility of the A6 and A9 cis-octadecenoates was proportional to the distance of the double bond from the carboxyl group (9). However the increased solubility that would result as the double bond is moved from carbon 9 to carbon 17 would not be correlated with the activation profile observed in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Thus Farmer & van den Heuvel (1938) have criticized the use of conventional vacuum-distillation techniques, and several authors have criticized the polybromide method on the grounds that structural alteration of such labile molecules can, and probably does, occur. Kolb & Brown (1955) have pointed out that the usefulness of low-temperature fractional-crystallization procedures may be limited by mutual-solubility effects.…”
mentioning
confidence: 99%
“…5. It is encouraging to relate these response surfaces with a classic study by Kolb and Brown [28], suggesting that longer reaction time and lower temperature relatively helps ease the low temperature solvent fractionation. With that, between the studied ranges of this paper, 8 to 24 h of crystallization time and from −15 ºC to 5 ºC of crystallization temperature have been proven efficient to separate USFA.…”
Section: Resultsmentioning
confidence: 69%